Influence of demographic characteristics, tooth loss, and tooth wear on condylar movements: Cross-sectional study - Soha Alratroot; Shahd Khan; Nora Alkaltham; Intisar Ahmad Siddiqui; Ahmad M. Al-Thobity (Elsevier, 2022)
Objectives: The study's aim was to assess and compare the values of the sagittal condylar angle (SCA), the Bennett angle (BA), and the immediate side shift (ISS) between fully dentate and partially dentate patients, male and female patients, and Saudi and non-Saudi patients. The study also aimed to statistically analyze the correlation of the different condylar movements with tooth loss and tooth wear. Materials and Methods: Using the electronic pantograph (Cadiax Compact II), the SCA, BA, and ISS were recorded at a 10-mm condylotrack distance in dentate and partially dentate patients, from both genders, older than 20 years, medically stable, and with normal temporomandibular joint movements and normal activity of masticatory muscles. The recorded average values were compared between the groups using an unpaired t-test. Results: The average condylar movements between dentate (n = 57) and partially dentate (n = 39) groups revealed no significant differences concerning right SCA, left SCA, right BA, right ISS, and left ISS. However, the left BA showed significant differences (P = 0.011) in the dentate compared with the partially dentate group. Gender (male: n = 24, female: n = 72) showed no statistical significance between groups when measuring SCA, BA, or ISS. When comparing Saudi (n = 78) with non-Saudi patients (n = 18), it was found that the mean right SCA was significantly higher in Saudi than in non-Saudi patients (P = 0.024). Condylar inclination values in relation to tooth wear showed no statistical significance (P > 0.05), except left ISS, which was significantly higher among those who had tooth wear (P = 0.040). Conclusion: Tooth loss had a major impact on the left BA, while patients with tooth wear had a significantly increased ISS on the left side.